KONTRIBUSI KEMAMPUAN BERPIKIR KOMBINATORIK DALAM PEMBELAJARAN STATISTIKA MATEMATIKA - Syahlan Syahlan; Dhia Octariani (Universitas Pekalongan, 2021)
Combinatoric ability allows the process of connecting several patterns and principles in formula discovery activities through generalizations to help students see the application of mathematics in real life. The model given can help in making broad rough estimates in developing their insights. The purpose of this study was to find out how combinatoric thinking skills are and whether combinatoric thinking skills contribute to mathematical statistics courses. This research belongs to the field of social sciences and can use this type of qualitative descriptive approach. The data were collected using a descriptive test which consisted of four items related to combinatoric problems. The data from the research results were processed using the SPSS program to get the contribution value of combinatoric thinking skills during the mid-test and final-test. with 23 students. The results of the analysis showed that the students' combinatoric thinking skills were quite good, where the mean and standard deviation were 71.27 and 6.09 during the middle exam and 72.00 and 5.88 at the time of the final exam. The problem that students have in combinatoric skills is the problem of mathematical modelling. The test results show that combinatoric thinking skills have a significant contribution to the mathematics-statistics course.